Att läsa egyptiska - Fredrik Thomasson (Lychnos, 2020)
The article traces Johan David Åkerblad’s contributions to one of the 19th century’s most famous scientific triumphs, the decipherment of hieroglyphs. Egyptology often counts its birth from 1822 when hieroglyphs first could be read; the focus here are on the preceding decades of Egyptian studies. Åkerblad, the son of a mirror-maker, was born in Stockholm in 1763. That he was born a commoner and supported radical political ideas was an important factor in his less than successful Swedish career. He was a precocious oriental linguist who already before leaving Uppsala university was well versed in classical languages as well as in Arabic and Turkish. Throughout his diplomatic postings in Constantinople between 1784 and 1797 he travelled widely in the Eastern Mediterranean. He knew the local languages well enough to travel in disguise.